Effect of storage and product making on the antioxidant activity of wheat - Narwal, Sneh; Jaswal, Sunita; Sehgal, Vijay Kumar; Sheoran, Sonia; Gupta, Raj Kumar (Journal of Cereal Research, 2012)
This study presents the results for the effect of storage, chapatti and pasta making on the antioxidant activity of wheat. There was about 25% reduction in the antioxidant activity after 60 days of storage at -20°C, 4°C and RT But, a sudden decrease in the activity was observed at 60°C within first fifteen days of storage. After making chapatti from the whole meal, a 30% reduction was observed in the antioxidant activity. Semolina production resulted in 45% reduction in the antioxidant activity. This reduction further continued during pasta making and in the final pasta product the antioxidant activity was reduced by 70%. Whole grain based food products like chapatti have more antioxidant activity than the refined products like semolina and pasta which do not contain the bran and the germ portion of the wheat. Therefore, there should be minimum processing of the grains before and during product making so as to have maximum health benefits.